Artificial Intelligence and E-Commerce: An Empirical Investigation of Daraz Pakistan - Muhammad, Jan; Kazi, Abdul Kabeer; Munir, Saira (Pakistan Languages and Humanities Review, 2023)
Artificial intelligence plays a vital role in the growth of the E-commerce industry. The e-commerce industry uses several artificial intelligence tools to promote its businesses. This study aims to examine the impact of artificial intelligence on the E-commerce activities of Daraz Pakistan. Primary data was gathered from 423 full-time customers and managerial-level employees of the Daraz throughout Pakistan. The data was gathered through convenience sampling. The gathered data was analyzed via SmartPLS. According to this study's findings, different artificial intelligence-based tools, such as chatbots, personal shopping assistance, easy search, fraud detection, and supply chain management, significantly impact Daraz's e-commerce activities. Furthermore, this study also recommends that Daraz increase the usage of artificial intelligence-based applications in their business activities to enhance further and reshape the business model to increase Daraz's profitability.